Existence and Stability Results for Coupled Fractional Dynamic System with Impulses over Non-uniform Time Domains - Kumar Vipin; Malik Muslim (Nonautonomous Dynamical Systems, 2022)
In this manuscript, we examine the existence, uniqueness and stability results for a coupled fractional dynamical system with impulsive and initial-boundary (IB) conditions on non-uniform time domains by implying the theory of time scales. Firstly, we find the solution of the consider problem, then we examine the existence and stability results. Mainly, we use the Banach and Leray-Schauder’s alternative type fixed point theorems to establish the main results. At last, we present an example to illustrate the utilization of these analytical outcomes.